Evaluation of one-house one-larvae observer program in controlling dengue hemorrhagic fever in Central Sulawesi - Koraag, Meiske Elisabeth; Samarang, Samarang; Nurjana, Made Agus; Octaviani, Octaviani; Widjaja, Junus; Massie, Roy Glen Albert (Intelektual Pustaka Media Utama, 2024)
Dengue hemorrhagic fever (DHF) is still a health problem in Poso District. This can be seen from the high number of DHF cases and potential outbreaks from 2017 to 2018. The local government took the initiative to prevent DHF outbreaks in Poso Regency. The Central Sulawesi Provincial Health Office and the Poso Regency Health Office have implemented onehouse one-larvae observer program in the Poso Kota Selatan District area by engaging the local government and community. The implementation of the program and its accomplishments requires evaluation. This study aims to evaluate the one-house one-larvae observer program using input, process, output, and outcome indicators. The research adopts a descriptive-qualitative approach, employing observation and interviews within an evaluation research design. Data analysis was performed using interpretation and triangulation methods. Policy documents are available, and human resources supporting the program are in compliance with the decree. However, the budget for the program is insufficient, while the available infrastructure is sufficient. The process indicators demonstrate satisfactory progress. Based on outputs, there was an increase in achievement against the program target of the number of buildings inspected by house larvae observers over four years. The outcome indicator in the form of the larvae-free rate increased by >90% during one year of program implementation. The implementation of local innovations initiated by the Regency Health Office and stakeholders’ engagement has been proven to increase community participation in programs that impact the achievement of program outputs and outcomes.